Sistem Penerimaan Dan Pengelolaan Administrasi Keuangan Pendidikan Di Kober TK Islamic Centre Berbasis WEB (Jurnal Kendali Akuntansi, 2023)
Administrative financial education is an important component in the field of education to obtain educational facilities, including in Kober TK Islamic Center. Recording of acceptance and management of school financial administration at the Kober TK Islamic Center using handwriting or has not been computerized, which can result in a lot of bookkeeping, writing errors, and delays in financial reporting. In addition to the long recording process, data search also takes a long time, which can make it difficult for administrative staff to process acceptance and manage financial administration. Based on the problems in the Kober TK Islamic Center, it is necessary to build an information system that can assist in recording and managing financial administration. This information system creates using the MySQL database, the PHP (Hypertext Preprocessor) programming language, and Sublime Text for the text editor. the test server uses XAMPP, and the data used is obtained from Kober TK Islamic Center. The expected results of this final project are to assist employees in recording acceptance and managing financial administration efficiently. Then, for this project, it is hoped that it can also assist in the acceptance and management of financial administration in the Kober TK Islamic Center.